A study on impact of privatization to the company performance: a case for Telekom Malaysia Berhad / Suria Suhaimi - Suhaimi, Suria (2009)
Telekom Malaysia Berhad (TM, MYX: 4863) is the largest telecommunication company in Malaysia and also Southeast Asia's second-largest telecommunication company. It has a monopoly on the fixed line network and has a considerable market share of the mobile communications market after its acquisition of Celcom and merging with its mobile operation arm, TMTouch. This exploration study was conducted out to study on the performance of Telekom Malaysia toward privatization. Tools that used to collect information were from secondary data such as internet. By study the current performance, it concluded that privatization is making the company better than before. Several advantages and disadvantages are finding to be useful for future research.